Evaluation of a Nylon 3D-Printed Wrist Splint Through Finite Element Analysis (FEA) and User-Based Assessment - Pratama, Juan; Anggara, Ardhito Yogie; Saputra, Ganang Arya; Sugiyanto, Didik; As'yari (Jurnal Rekayasa Mesin, 2025)
A wrist splint is a medical assistive device designed to limit wrist movement and provide structural support during post-operative rehabilitation. This study investigates the applicability of 3D printing technology for the fabrication of a customized wrist splint. Finite element analysis (FEA) was carried out to evaluate the mechanical performance of a nylon-based 3D-printed wrist splint, while a user assessment involving ten respondents was conducted to compare the 3D-printed prototype with the commercially available alternatives. The analysis revealed that the 3D-printed nylon splint could sustain loads well above the maximum force generated by human muscles, with normal and von-Mises stresses representing only 5.25% and 7.9% of the material’s ultimate tensile strength (UTS), and maximum flexural stress corresponding to merely 1.4% of its ultimate flexural strength (UFS). Based on user assessment, the 3D-printed splint outperformed commercial ones in terms of lightness, comfort, functionality, and stiffness, though it was less favorable in price and ease of use. Additionally, the findings indicate that the nylon-based 3D-printed wrist splint adequately satisfies the fundamental functional requirements of a wrist support device. Eventually, the results affirm the significant potential of 3D printing technology as a reliable and customizable manufacturing approach for wrist splint application.